Meningkatkan high order thinking skills mahasiswa semester III PPKn dalam pembelajaran Psikologi Sosial melalui penerapan metode six thinking hats - Chotimah, Umi; Nurdiansyah, Edwin (Universitas Negeri Yogyakarta, 2017)
This study was aimed at increasing High Order Thinking Skills (HOTS) of third semester Citizenship Education (CE) students in Social Psychology of Learning course through the application of Six Thinking Hats Method (STH). This research was conducted using the method of classroom action research, which were carried out by two cycles, with the subject of the study were all students of the third semester CE study program class who participated in the course of Educational Psychology. Based on the analysis and discussion, it can be concluded that through the application of Six Thinking Hats method can increase (HOTS). This was evident from the increase in test scores that have been designed to measure students' critical thinking skills, where achievement test scores in the moments before the implementation of learning using STH method only in the range of 46.0, then after the first cycle increased to 53.9 and at the end of the second cycle increased to 69.8, meaning increased 23.9 points. Furthermore, the observation also showed improvement in the students' ways of thinking, indicated by the students began to be able to think critically after the learning process in the classroom using the STH.